Three Seas Initiative and Ukrainian Seaports’ Prospects amid Russian Aggression - Dariia Bilenets; Halyna Ulianova; Kristina Vozniakovska (Lex Portus, 2022)
After the outbreak of the Russian invasion in 2022, Ukraine indicated its desire to participate in the regional European Three Seas Initiative. The initiative’s basic ideas generally correspond to Ukraine’s interests and capabilities as a transit state. The significant potential of the Ukrainian port infrastructure makes Ukraine’s participation in TSI projects promising. At the same time, the prospects for the port industry in Ukraine can develop according to two different scenarios, directly determined by the course of the Russian-Ukrainian armed conflict and its results. Although already at this stage, providing Ukraine with new integration opportunities within the EU and changes in the EU transport policy can create the foundation for broad participation in TSI projects.